Small Molecule Inhibitors of HSF1-Activated Pathways as Potential Next-Generation Anticancer Therapeutics - Chiranjeev Sharma (Molecules, 2018)
Targeted therapy is an emerging paradigm in the development of next-generation anticancer drugs. Heat shock factor 1 (HSF1) has been identified as a promising drug target because it regulates several pathways responsible for cancer cell growth, metastasis, and survival. Studies have clearly demonstrated that HSF1 is an effective drug target. Herein, we provide a concise yet comprehensive and integrated overview of progress in developing small molecule inhibitors of HSF1 as next-generation anticancer chemotherapeutics while critically evaluating their potential and challenges. We believe that this review will provide a better understanding of important concepts helpful for outlining the strategy to develop new chemotherapeutic agents with promising anticancer activities by targeting HSF1.